Pengembangan Program Studi Berkelanjutan Pada MBKM Dengan Penerapan SWOT Analisis dan BMC - Efta Dhartikasari Priyana (Jurnal Serambi Engineering, 2022)
The existence of the MBKM program promoted by the Minister of Education has shifted the existing curriculum. The aim is none other than to improve the competence of graduates, both soft skills and hard skills, to be more prepared and relevant to the needs of the times. Prepare graduates as future leaders with excellent and personality. There are about 8 programs carried out by the government. This research is amazed at the development of the Sustainable Study Program at MBKM with the Application of SWOT Analysis and BMC. The results of the IE matrix are in quadrant V, namely (1) maintaining existing Study Programs while managing the management of existing Study Programs according to MBKM directions; (2) use opportunities within the PT Muhammadiyah association to build a joint cooperation program; (3) using existing partner radar to reach partners outside the study program's reach; (4) Strengthening cooperation between Study Programs within the campus, to build the reach of partnerships between fields; (4) Strengthening cooperation between Study Programs within the campus, to build the reach of partnerships between fields. As for BMC, the results are (1) Study Program X can prepare a curriculum according to MBKM directions before joining the MBKM program; (2) Study Program X captures the existing potential, which here is to expand the partner network for Tri Darma or laboratories; (3) Study Program X has more potential for alumni and surrounding companies, to attract many interested people.